Accuracy of Teledentistry for Diagnosis and Treatment Planning of Pediatric Patients during COVID-19 Pandemic - Ozra Golsanamloo; Sanaz Iranizadeh; Amir Reza Jamei Khosroshahi; Leila Erfanparast; Ali Vafaei; Yalda Ahmadinia; Solmaz Maleki Dizaj (International Journal of Telemedicine and Applications)
Teledentistry is a new technology in the dentistry field, which has great benefits during pandemic such as the coronavirus disease 2019 (COVID-19). The overall purpose of the study was to assess the diagnostic sensitivity and specificity of virtual (mobile phone teledentistry) compared with clinical examinations during COVID-19. The basic design of the study was based on the comparison treatment plans by the students and the gold standard (clinical treatment plan of an expert pedodontist with 10 years of clinical experience). This double-blind clinical trial was conducted on 20 children (aged 6 to 12 years) with a chief complaint of dental caries with or without pain. An appropriate radiograph and five standard intraoral photographs (frontal view occlusion, maxillary occlusal view, mandibular occlusal view, right lateral view, and left lateral view) were prescribed for each patient according to the guidelines of the American Association of Pediatric Dentistry. Then, the treatment plan for the carious teeth was recorded for each patient. Each patient underwent a clinical examination at first and was followed randomly by a virtual examination by two dental students. Then, the clinical and virtual treatment plans were compared with each other, and also with the gold standard. The sensitivity and specificity values were calculated for each group. The accuracy of the diagnosis was measured by applying Cohen’s kappa. Interexaminer reliability was measured using the intraclass correlation coefficient (ICC) and Cronbach’s alpha. The mean kappa coefficient for the interexaminer agreement (for 24 teeth) was 0.62 in clinical and 0.69 in virtual examinations. The results showed no significant difference in the treatment plans of students and the gold standard (P>0.05). The diagnostic sensitivity and specificity were 73.22% and 95.8% for clinical and 76.44% and 92.9% for virtual treatment plans showing no significant differences between virtual (mobile phone teledentistry) and clinical examinations (P>0.05). The intraexaminer reliability of the examiners was found to be 0.92 by calculating the ICC. Then, teledentistry can be considered as a supplement to clinical examinations of pediatric dentistry, finally resulting in better patient management. However, more studies are necessary for teledentistry.